Blade Element Momentum Method for a Counter-Rotating Pump-Turbine - Ibanez Uribe, Cristobal (My University, 2021)
Blade Element Momentum (BEM) methods are widely used for initial aerodynamic analysis of wind and tidal turbines, as well as aircraft and marine propellers. Mainly because they use less computational resources and can give fairly accurate results. This thesis studies the applicability of such method for load prediction on the runner blades of a model scale axial shaft-driven Counter-Rotating Pump-Turbine (CRPT). One of the main assumptions and modifications adopted in the BEM method was to omit the axial induction factor, a ,and let the axial velocity be constant. This considering that the volumetric flow rate, q, and cross-sectional area, A, must remain unchanged throughout the turbomachine. Additionally, an attempt to include the constant pressure difference across the rotors as extra loading being exerted on the blade, as well as a suggestion on how to apply the BEM method on the downstream rotor are presented and evaluated. The data needed to implement the BEM method is created by running several CFD simulations using OpenFOAM. These simulations produce 2D aerodynamic airfoil-like characteristics of lift and drag coefficients, Cl and Cd, at different angles of attack (AoA) and Re numbers in both pump and turbine mode for different blade profiles along the radial direction. Furthermore, validation cases at different operating conditions are also simulated with OpenFOAM assuming steady-state flow. This is done for different geometries. One of them considers the turbomachine with both runners operating simultaneously and the other geometries isolate each runner individually. It is concluded that it is possible to use the BEM method with a reasonable amount of error for certain operating conditions. Most importantly the behaviour of the dimensionless thrust and power coefficients, CT and CP at different tip speed ratios, T SR, tends to follow the same trend as CFD. Further work needs to be done in order to fully validate such a method for this type of turbomachine.
Keywords: BEM, CFD, Counter-Rotating, Pump-Turbine, Hydro-power, Open-FOAM